Acute low grade fever and atypical pneumonia in Asian’s epidemic area-melioidosis is an unequivocally important diagnostic differential - Abdullah, Noraini Sarina; Ahmad Saad, Fathinul Fikri; Mohamed Said, Shahrir (OMICS International, 2015)
Background: High grade fever and atypical pneumonia in a susceptible Asian epidemic area could construe fatal consequences attributable to specific prevalence factitious organism: i.e Bukholderia pseudomallei.